2012
DOI: 10.1055/s-0031-1298625
|View full text |Cite
|
Sign up to set email alerts
|

Library-based Discovery of DYRK1A/CLK1 Inhibitors from Natural Product Extracts

Abstract: The dual specificity tyrosine-phosphorylation-regulated kinase DYRK1A possesses diverse roles in neuronal development and adult brain physiology, and increased activity has been linked to neurodegenerative diseases. Very few inhibitors of this kinase have been reported up to now. Screening of a library of > 900 plant and fungal extracts afforded 25 extracts with IC₅₀s < 10 µg/mL against DYRK1A. To identify the active constituents, the extracts were submitted to a process integrating physicochemical data with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Some compounds have been identified as both Clk and Dyrk inhibitors, such as, 6-arylquinazolin-4-amine analogs, 5,12,13 leucettines, 14 bauerine C derivatives, 15 a benzothiazole analog, 16 and natural product extracts. 2 However, development of potent and selective Clk and Dyrk inhibitors is still yet to be explored. 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Some compounds have been identified as both Clk and Dyrk inhibitors, such as, 6-arylquinazolin-4-amine analogs, 5,12,13 leucettines, 14 bauerine C derivatives, 15 a benzothiazole analog, 16 and natural product extracts. 2 However, development of potent and selective Clk and Dyrk inhibitors is still yet to be explored. 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Given the structural diversity of the alkaloids included in this study, deriving structural features critical for hERG inhibition was not possible. However, it seems that alkaloids with an aporphine (17)(18)(19)(20) or benzophenanthridine (21)(22)(23)(24) scaffold are particularly prone to hERG block.…”
Section: Resultsmentioning
confidence: 99%
“…Sivaraman et al () also revealed that kaempferol ( 20 ) has a good binding affinity with the target AChE enzyme, suggesting an anti‐AD effect. By screening of a library of more than 900 plant and fungal extracts, kaempferol ( 20 ) from C. chinensis showed a significant inhibitory effect in tyrosine‐phosphorylation‐regulated kinase DYRK1A with an IC 50 value of 0.91 μM, which will help neuronal development and adult brain physiology (Grabher et al, ).…”
Section: Phytochemistrymentioning
confidence: 99%